Seres invisíveis - XADALU, Dione Martins da Luz (Paralelo 31, 2019)
O presente ensaio visual reúne os retratos de indivíduos da etnia guarani produzidos por Xadalu para a série Seres Invisíveis (2016) e as imagens da intervenção urbana realizada a partir da colagem dessas fotografias como cartazes em vários pontos do centro de Porto Alegre, RS, Brasil. Invisible beingsAbstract:The present visual essay brings together the portraits of Guarani individuals produced by Brazilian artist Xadalu for his Invisible Beings series (2016) and also images of the urban intervention made from the collage of these photographs as posters placed in various spots in downtown Porto Alegre, the capital city of Rio Grande do Sul state in southern Brazil.